Hilando la historia se teje la ruana: hacia la comprensión de didácticas de la Investigación – creación a través de narrativas de identidad sociocultural del campesino del altiplano cundiboyacense (2022)
In the uncertainties lived of this research process, the artists teachers- researchers had enhanced a detailed insertion to comprehend the creation didactics that enable the realization of interdisciplinary productions, located in the study of sociocultural representations. This creationresearch is developed with the members of Colectivo Artístico Backú, through creation labs. In a general manner in this research is concluded that, the interpretation of the method of collective creation, the conceptual inquiry, the experiences of the sociocultural context of the ruana the principle of significance, motivation, sensitivity of artists in training the principle of contextuality allows the creation of an interdisciplinary montage with a conflict that addresses the permanence or disappearance of the ruana. Theoretical contextualization, motivation, experience and the learning process are elements of a didactic order that contribute to creation. The relations built in the creation and the didactic principles are the ones that allow the development of different reflections that enhance the creative act.